Inclusion and Integration of Youth Needs in Youth Empowerment Programmes: A Mixed-Method Study of Nairobi and Trans Nzoia Counties - Catherine Mbugua; Karuti Kanyinga; Paul Mbatia (European Scientific Journal, ESJ, 2024)
The youth bulge, a rapid population increase among young people caused by reduced infant mortality without a corresponding decrease in fertility rates, has recently become a pressing reality in Africa. It has triggered calls for concerted efforts from all development actors in the continent to ensure that youths are engaged in meaningful socio-economic and political advancement in their respective nations. As a result, many state and non-state youth empowerment programmes (YEPs) have been developed in Kenya over the last two decades, even as concerns continue to be raised about their efficacy and sustainability. This paper focuses on exploring the extent of youth inclusion and the integration of youth needs in YEPs in two counties: Nairobi, an urban setting, and Trans Nzoia, a rural setting. The study adopted a mixed-method research approach.  First, a comparative youth survey was conducted in Nairobi and Trans Nzoia counties. The cross-sectional survey involved 244 youth respondents in the two counties and was complemented by Focus Group Discussions (FGDs), key informant interviews, and observation. Descriptive analysis through SPSS and thematic analysis were used to analyze the quantitative and qualitative data, respectively. The study established that youths participating in Youth Empowerment Programmes (YEPs) are primarily engaged as groups, rather than as individuals. In addition, youth inclusion in YEPs is generally lacking, with a majority of participants in both counties, 53.1% in Nairobi and 59.7% in Trans Nzoia, disagreeing with the statement that youth have a say in the programmes run in their respective areas. Regarding the integration of youth needs, the study found that young people experience limitations in accessing finance and support from programme officers. The study recommends enhancing avenues for youth engagement to facilitate greater efficacy in the conceptualization and execution of YEPs in Kenya.